Contemporary arts practice: Disequilibrium/Limbo/Resistance - Green, Miik Wardman (Curtin University, 2014)
This exegesis proposes that conflict and tension are transformative factors in contemporary arts practice, from making through to methodologies; viewing the dialogic nature of art-making and the artist-in-the-world, linked to, yet separate from, surrounding entities. It is the culmination of conceptual research and creative production … the exegetical and the artwork … that together comprise an original contribution to new knowledge, with broad implications - and specific applications - significant to both practice and practitioner.